How Does Our Knowledge on the Na+/H+ Exchanger NHE1 Obtained by Biochemical and Molecular Analyses Keep up With Its Recent Structure Determination? - Poet, Mallorie; Doyen, Denis; Van Obberghen, Emmanuel; Jarretou, Gisèle; Bouret, Yann; Counillon, Laurent (Frontiers in Physiology, 2022)
Na+/H+ exchangers are membrane transporters conserved in all living systems and therefore are assumed to be amongst the most ancestral molecular devices that equipped the first protocells. Following the cloning and sequencing of its gene, the mammalian NHE1, that regulates pH and volume in all cells, has been thoroughly scrutinized by molecular and biochemical analyses. Those gave a series of crucial clues concerning its topology, dimeric organization, pharmacological profile, regulation, and the role of key amino acids. Recently thanks to cryogenic Electron Microscopy (Cryo-EM) the long-awaited molecular structures have been revealed. With this information in mind we will challenge the robustness of the earlier conclusions and highlight how the new information enriches our understanding of this key cellular player. At the mechanistic level , we will pinpoint how the NHE1 3D structures reveal that the previously identified amino acids and regions are organized to coordinate transported cations, and shape the allosteric transition that makes NHE1 able to sense intracellular pH and be regulated by signaling pathways.